ECONOMIC EMPOWERMENT POLICIES TO FIGHT POVERTY AND INEQUALITY - Jackson Yumame; Loso Judijanto; Oggy Akmadani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Economic Empowerment Policy to Fight Poverty and Inequality is a comprehensive approach that aims to address two major social problems faced by many countries. The review method in this research uses literature. The results of this study found the importance of access to education, job training, support for micro, small and medium enterprises (MSMEs), and the need for policy reforms that prioritize welfare and social justice as the main keys to achieving economic growth that is not only fast, but also equitable and fair for all levels of society.